A new species of Tricorythopsis Traver, 1958 (Leptohyphidae) and occurrence of Pannota (Insecta: Ephemeroptera) species in Amapá state, Brazil - Belmont, Enide Luciana L.; Cruz, Paulo Vilela; Hamada, Neusa (Zootaxa, 2015)
The objectives of this study were to describe a new species of Tricorythopsis based on adults, and to report for the first time the following species and genera in Amapá state, Brazil: Amanahyphes saguassu Salles & Molineri, Macunahyphes australis (Banks), Macunahyphes pemonensis Molineri, Grillet, Nieto, Dominguez & Guerrero, Tricorythodes yapekuna Belmont, Salles & Hamada, Tricorythopsis faeculopsis Belmont, Salles & Hamada, Tricorythopsis pseudogibbus Dias & Salles, Tricorythopsis rondoniensis (Dias, Cruz & Ferreira), Tricorythopsis yucupe Dias, Salles & Ferreira (Leptohyphidae), Coryphorus aquilus Peters (Coryphoridae) and Brasilocaenis (Caenidae). Macunahyphes pemonensis is recorded for the first time in Brazil. Tricorythopsis yusuaia sp. nov., can be distinguished from congeners by the following combination of characteristics: abdomen with black and reddish marks, a strongly sclerotized spine present on the base of the median filament, and the base and lateral margins of penes being sclerotized.